Dual-beam electromagnetically-induced absorption resonance in a 87Rb cell with antirelaxation coating. Issue 1 (March 2021) - Taskova, E; Alipieva, E
Abstract: Destruction of the laser-induced coherence in the ground state of alkali atoms manifests itself as an ultra-narrow resonance in the atomic spectrum. Depending on the geometry of irradiation and observation, the coherent spectroscopy studies CPT (coherent population trapping), EIT (electromagnetically-induced transparency) or EIA (electromagnetically-induced absorption). In the present work, we investigated EIA on the D1 87 Rb line by applying a counter-propagating dual-beam scheme. The main advantage of this scheme is the high resonance contrast – an important parameter for many applications. In our previous work performed in a paraffin-coated cell we observed that, unlike the resonance in buffer gas cell detected in the same experimental scheme, the EIA signal has a complex form, because it is formed by two atomic sub-ensembles in the vapor cell with different relaxation rates determined by the laser excitation conditions. We focused on the narrow component, since it has a higher amplitude-width ratio, making it preferable for applications. We investigate the influence of the atomic vapor density and the pump laser intensity on the resonance parameters in order to optimize the amplitude ratio of the wide and narrow components and achieve the highest amplitude-width ratio value for the narrow component of the EIA resonance.